NALISIS KINERJA KEUANGAN PADA PT. GRAND VICTORIA HOTEL DI SAMARINDA - ., Atmajaya (EKONOMIA, 2013)
Based on the results of analysis show that the performance of PT. Hotel Grand Victorian is measured using liquidity ratios and profitability ratios decreased from 2010-2012. Performance PT. Grand Victorian is measured using the liquidity ratio has decreased from year 2010-2012 consists of current ratio has decreased, and this is because the total current assets has increased and decreased. Meanwhile, the cash ratio from year 2010-2012 has increased, this is because the total cash and cash equivalents increased. Performance PT. Hotel Grand Victorian is measured using profitability ratios decreased from the year 2010-2012 consists of gross profit margin has decreased , this was due to the increase in gross profit is smaller than the increase in operating revenue. Operating profit margin has decreased, this was due to an increase in income before income tax is less than the increase in operating revenue. Net profit margin has decreased, this was due to the net profit after income tax increase is greater than the increase in operating revenue. The total assets turnover has decreased, this was due to the decrease in total assets is greater than the increase in operating revenue. Return on investment has decreased, this was due to an increase in total assets is greater than the increase in net profit after income tax. The hypothesis of this was rejected because of the financial performance. Hotel Grand Victorian is measured using liquidity and profitability ratios decreased from 2010 to 2012